Pengembangan English for Tourism pada Program Destinasi Pariwisata: Perspektif ESP dan Implikasi Pedagogis - Marcha Stephanie Inapratama Matitaputty; Meiti Leatemia (Scholars, 2025)
This study aims to examine the English language needs of Destination Tourism students from the perspective of English for Specific Purposes (ESP) and to explore its pedagogical implications for vocational education. This study employs a conceptual approach through a literature-based analysis of ESP theory, communicative competence, and language needs in the tourism industry. The findings indicate that students primarily require functional oral communication skills, mastery of professional genres such as destination promotion and complaint handling, and intercultural competence in tourism service contexts. Furthermore, the diverse English proficiency backgrounds of students necessitate an adaptive, progressive, and task-based instructional design. The pedagogical implications highlight the importance of industry-oriented curriculum development, the implementation of authentic task-based learning, and performance-based assessment to enhance students’ workplace readiness. Therefore, the development of English for Tourism in vocational education must be contextualized and responsive to both professional demands and learner characteristics.Keywords: English for Specific Purposes, language needs, vocational education, tourism, course design